Views and Value of an Undergraduate General Education on Advancing Student Attitudes and Engagement - Strzalkowski, Nicholas D. J.; Sobhanzadeh, Mandana (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2023)
The enhancement of science literacy is a long-standing educational goal of liberal education programs. We conducted a mixed methods study to investigate undergraduate students’ attitudes towards science and engagement with science, with specific interests in students’ program (science vs. nonscience), level of study (junior: first and second year vs. senior: fourth year and higher), and changes over the duration of a single general education science literacy course (pre vs. post). Data were collected through an online questionnaire (n=272) and semi-structured interviews (n=8). We found that self-assessed science literacy was higher in students at the end of the course compared to at the beginning, in senior students compared to junior students, and for science students compared to nonscience students. Interest in learning about science topics was high overall, but did not increase over a single general education science literacy course or in senior compared to junior students. Belief in pseudoscience was also high overall, including in senior and science students, groups in which we expected pseudoscience belief to be lower. Views about science were generally favourable but were not improved by the science literacy course. This work highlights the need to align science curriculum with students’ interests while differentiating science from pseudoscience topics. Findings demonstrate the importance of engaging nonscience majors, who may have less intrinsic interest in science topics and can hold less favourable views about the value of science in their lives. As the last time when most students are formally exposed to science concepts and methods, undergraduate education is critical to promoting individual and societal science literacy.